2016
DOI: 10.1111/cote.12253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the water content of padded cotton fabrics on reactive dye fixation in the pad‐steam process

Abstract: A series of padded cotton fabrics with various water contents were obtained through vacuum dehydration. The effects of the water content on the fabric temperature variation during steaming, the colour properties, and the dye fixation rate (%F) were investigated. Dye distribution in the dyed cotton fibres was assessed. The influences of steaming time and sodium carbonate concentration on K/S value and %F of the dyed fabrics with low water content were also evaluated. The results indicate that reducing the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Unfortunately, in the presence of moisture, the thermal insulation for such products is drastically reduced-if the padding is exposed to water and the surface fabric is not properly isolated, the thermal insulation drops to zero [3]. Moreover, multilayer materials filled with feathers are expensive and, often, the origin of natural material often involves the presence of impurities or substances dangerous to health.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in the presence of moisture, the thermal insulation for such products is drastically reduced-if the padding is exposed to water and the surface fabric is not properly isolated, the thermal insulation drops to zero [3]. Moreover, multilayer materials filled with feathers are expensive and, often, the origin of natural material often involves the presence of impurities or substances dangerous to health.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that the water content of the fabric is of great significance to the fixation of reactive dyes, while only a few studies in this territory have been reported previously. 17,18 Zhiping et al. 18 studied the mechanism and diffusion model of reactants in low add-on technologies.…”
mentioning
confidence: 99%
“…19 Kuanjun et al. 17 studied the temperature variation of the fabric being vacuum dehydrated during saturated steaming and found that reducing the water content of padded cotton fabrics before steaming could enhance the color depth and fixation rate. These provide a theoretical basis for the study of low add-on technologies.…”
mentioning
confidence: 99%
See 2 more Smart Citations